Analysis of odd-mass technetium isotopes with the Alaga model - Abecasis, Sara Mabel (1976)
The structure of the odd-mass technetium isotopes is analyzed with the Alaga model which involves the coupling of a three-particle valence-shell cluster to the quadrupole vibrational field. The calculated energy-level sequence and decay properties are consistent with the general trend of the available experimental information although no attempt of the best fit to individual properties was pursued.